Aegilops umbellulata introgression carrying leaf rust and stripe rust resistance genes Lr76 and Yr70 located to 9.47-Mb region on 5DS telomeric end through a combination of chromosome sorting and sequencing - Bansal, Mitaly; Adamski, Nikolai M; Toor, Puneet Inder; Kaur, Satinder; Molnár, István; Holušová, Kateřina; Vrána, Jan; Doležel, Jaroslav; Valárik, Miroslav; Uauy, Cristobal; Chhuneja, Parveen (Theoretical and Applied Genetics, 2020)
KEY MESSAGE: Lr76 and Yr70 have been fine mapped using the sequence of flow-sorted recombinant 5D chromosome from wheat-Ae. umbellulata introgression line. The alien introgression has been delineated to 9.47-Mb region on short arm of wheat chromosome 5D. Leaf rust and stripe rust are among the most damaging diseases of wheat worldwide. Wheat cultivation based on limited number of rust resistance genes deployed over vast areas expedites the emergence of new pathotypes warranting a continuous deployment of new resistance genes. In this paper, fine mapping of Aegilops umbellulata-derived leaf rust and stripe rust resistance genes Lr76 and Yr70 is being reported. We flow sorted and paired-end sequenced 5U chromosome of Ae. umbellulata, recombinant chromosome 5D (5DIL) from wheat-Ae. umbellulata introgression line pau16057 and 5DRP of recurrent parent WL711. Chromosome 5U reads were mapped against the reference Chinese Spring chromosome 5D sequence, and alien-specific SNPs were identified. Chromosome 5DIL and 5DRP sequences were de novo assembled, and alien introgression-specific markers were designed by selecting 5U- and 5D-specific SNPs. Overall, 27 KASP markers were mapped in high-resolution population consisting of 1404 F5 RILs. The mapping population segregated for single gene each for leaf rust and stripe rust resistance. The physical order of the SNPs in pau16057 was defined by projecting the 27 SNPs against the IWGSC RefSeq v1.0 sequence. Based on this physical map, the size of Ae. umbellulata introgression was determined to be 9.47 Mb on the distal most end of the short arm of chromosome 5D. This non-recombining alien segment carries six NB-LRR encoding genes based on NLR annotation of assembled chromosome 5DIL sequence and IWGSC RefSeq v1.1 gene models. The presence of SNPs and other sequence variations in these genes between pau16057 and WL711 suggested that they are candidates for Lr76 and Yr70.
Keywords: šlechtění rostlin; mapování chromozomů; Basidiomycota; genová introgrese; rekombinace genetická; Polymorphism, Single Nucleotide; fenotyp; Genetic Markers; nemoci rostlin; genetické markery; Triticum; Chromosomes, Plant; jednonukleotidový polymorfismus; telomery; Phenotype; Aegilops; Plant Leaves; vysoce účinné nukleotidové sekvenování; Genetic Introgression; odolnost vůči nemocem; Plant Diseases; High-Throughput Nucleotide Sequencing; Recombination, Genetic; pšenice; Genes, Plant; Chromosome Mapping; Disease Resistance; Telomere; rostlinné geny; listy rostlin; Plant Breeding; chromozomy rostlin